WHY ENGLISH? THE CULTURAL LEGACY POPULAR MUSIC INTERNATIONAL TRAVEL INTERNATIONAL SAFETY - Ochilov, Navro’zbek (Maktabgacha taʼlim jurnali, 2023)
"In the era of globalization, English proficiency is becoming increasingly important, not only from an economic perspective but also from a cultural one. It allows people to better understand and appreciate the nuances of different cultures, build stronger relationships with people from diverse backgrounds, and promote greater empathy and understanding across borders." Dr. Shinya Yamanaka, Stem Cell Researcher and Nobel Laureate.